Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have some homework I can't seem to figure out. The assignment causing problems is devided into two parts; The first is to determine the inverse formula for a given formula (so the S = F'). The second part asks me to simplify the answer to the first question. I've looked trough all materials I have, but I can't figure out what happens here:

(I've used the ' symbol as NOT)

The first formula is as follows:

(a·c·(b + d) + b·c'·d + a'·b)

Which, when i invert it without simplifying, results into:

(a' + c' + b'·d')·(b' + c + d')·(a + b')

So far, so good. However, when I look at the given solution for the second part of the assignment, I can't seem to figure out the logic behind the given steps.

  (a' + c' + b'·d')·(b' + c + d')·(a + b')
= (a'·b' + a·c' + b'·c' + a·b'·d' + b'·d')·(b' + c + d') =
= (a'·b' + a·c' + b'·c' + b'·d')·(b' + c + d')
= a'·b' + a·b'·c' + b'·c' + b'·d' + a'·b'·c  + b'·c·d' + a'·b'·d' + a·c'·d' + b'·c'·d'+ b'·d' =
= a'·b' + b'·c' + b'·d' + a·c'·d

Can anyone point me in the direction of what steps are taken here? Thanks in advance!

share|improve this question

1 Answer 1

up vote 3 down vote accepted

Let me try this-- I have added two additional step in bold to make the steps clear.

$(a' + c' + b'·d')·(b' + c + d')·(a + b')$

$=\mathbf{(a' + c' + b'·d').(a + b')·(b' + c + d')}$ (by coomutativity of $.$)

$= (a'·b' + a·c' + b'·c' + \underline{a·b'·d' + b'·d'})·(b' + c + d')$ (multiplying and rearranging the first two factors; commutativity and associativity of $.$ and $+$, just like addition and multiplication of real number, being used )

$= (a'·b' + a·c' + b'·c' + \underline{b'·d'})·(b' + c + d')$ (using $\mathbf{x+x.y}=x:(1+y)=x.1\mathbf{=x}$ in the underlined)

= a'·b' + a·b'·c' + b'·c' + b'·d' + a'·b'·c + b'·c·d' + a'·b'·d' + a·c'·d' + b'·c'·d'+ b'·d' (multiplying and rearranging just like one step above; also $x.x=x$ has been used in all the 2-product terms)

$=\mathbf{a'.b'+\underline{b'.c'.a+b'.c'}+\underline{b'.d'+b'.d'.(a'+c+c')}+a.c'.d}$ (note that $b'.d'+b'.d'=b'.d'$ as $x+x=x\quad\forall x$; also the rearrangement is for the next step)

$= a'·b' + b'·c' + b'·d' + a·c'·d$, using the rule $x+x.y=x$ with $x=b'.c', y=a$ in the first underline and $x=b'.d', y=(a'+c+c')$ in the second underline.

share|improve this answer
    
Sorry in the third line I missed the term $a′.a$ in the first factor. Please note that $a′.a=0$ and $0+a=a\quad\forall a$, so this term will have no contribution in later steps :) –  Tapu Nov 1 '11 at 11:12
    
Still stared at it for about an hour, but i see what happens now. The reordering makes the samples real hard to understand, mainly because is isn't stated that reordering has taken place. Thanks for explaining! –  Lg102 Nov 1 '11 at 11:59
    
In such cases, you are welcome to ask what is the difficulty in which step. Just for an alternate easy way to Boolean algebra, may I know if you have read basics operations of set theory? The rules are exactly the same in both cases: $(U,\phi, \cup, \cap,')$ in set theory is exactly same as $(1,0,+,.)$ in Boolean algebra. So, if have read one, the other is obviously done (this is true for basic operations though). –  Tapu Nov 1 '11 at 12:26

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.